ACE I/D and A2350G Polymorphisms are Correlated with Body Mass Index, but Not with Body Weight and Essential Hypertension: Study in Javanese Postmenopausal Women - Utami, Sri Lestari; Simamora, Dorta; Idawati, Ira; Widjaja, Jimmy Hadi (Cell and BioPharmaceutical Institute, 2024)
Background: Genetics was one of the risk factors for essential hypertension (EH). Research on ACE I/D and A2350G polymorphisms associated with risk factors for hypertension in Indonesia has never been done. Therefore, this study was conducted to analyze the relationship between the genotype and alleles of this gene with EH, body weight, and body mass index (BMI) in Javanese postmenopausal women.Materials and methods: This cross-sectional study involved 69 postmenopausal Javanese women according to several criteria related with hypertension risk factors. The data were obtained from the measurement and questionnaire results, along with Towards Health Card Records. The polymerase chain reaction (PCR) genotyping method used was the restriction fragment length polymorphism and allele-specific.Results: The prevalence of hypertension, prehypertension, and normotension in Javanese postmenopausal women were 0.246, 0.13, and 0.623, respectively. The frequency of BMI classification as underweight, normal, overweight, or obese were 0.029, 0.42, 0.261, and 0.29, respectively. The ACE I/D and A2350G polymorphism variant genotypes and frequencies found were II (0.464), ID (0.522), DD (0.014), and AA (1). Meanwhile, the alleles and their frequencies at ACE I/D gene polymorphism were I (0.725) and D (0.275). The II and ID genotype was mostly found in normotension subjects. The DD genotype was only available in hypertension subjects. There was no association between genotypes and alleles of ACE I/D, hypertension, body weight, and BMI classification (p>0.05). There was an association between these genotypes, alleles, and BMI (p<0.05).Conclusion: ACE I/D polymorphism is susceptible for BMI in Javanese postmenopausal women.Keywords: Javanese postmenopausal, essential hypertension, ACE I/D, ACE A2350G